C1R Mutations Trigger Constitutive Complement 1 Activation in Periodontal Ehlers-Danlos Syndrome - Gröbner, Rebekka; Kapferer-Seebacher, Ines; Amberger, Albert; Redolfi, Rita; Dalonneau, Fabien; Björck, Erik; Milnes, Di; Bally, Isabelle; Rossi, Veronique; Thielens, Nicole; Stoiber, Heribert; Gaboriaud, Christine; et al. (Frontiers in Immunology, 2019)
Missense or in-frame insertion/deletion mutations in complement 1 subunits C1r and C1s cause periodontal Ehlers-Danlos Syndrome (pEDS), a specific EDS subtype characterized by early severe periodontal destruction and connective tissue abnormalities like easy bruising, pretibial haemosiderotic plaques and joint hypermobility. We report extensive functional studies of sixteen C1R mutations associated with pEDS by in-vitro overexpression studies in HEK293T cells followed by western blot, size exclusion chromatography and surface plasmon resonance analyses. Patient-derived skin fibroblasts were analyzed by western blot and Enzyme-linked Immunosorbent Assay (ELISA). None of the pEDS mutants was integrated into the C1 complex but cause extracellular presence of catalytic C1r/C1s activities. Overexpression experiments showed domain-specific abnormalities of intracellular processing and secretion with preservation of serine protease function in the supernatant. In contrast to C1r wild type, and with the exception of a C1R missense mutation disabling a C1q binding site, pEDS mutations had different impact on the cell: retention of C1r fragments inside the cell, secretion of aggregates, or a new C1r cleavage site. Overexpression results are in line with western blot analyses of patient fibroblasts showing decreased levels of secreted C1r. Importantly, all available patient fibroblasts exhibited activated C1s and activation of externally added C4 in the supernatant while control cell lines secreted proenzyme C1s and showed no increase in C4 activation. The central elements in the pathogenesis of pEDS appear to be the intracellular activation of C1r and/or C1s, and extracellular presence of activated C1s that independently of microbial triggers can activate the classical complement cascade.